Rancang Bangun Media Promosi Oleh-Oleh Khas Sampit Berbasis Website - Siregar, Rayanti Veronica; Christian, Efrans; Saputra, Ade Chandra (Journal of Information Technology and Computer Science, 2021)
Sampit is famous for its river called the Mentaya River, and has an icon, namely the Jelawat fish. This fish is one of the sources of income in several production houses as the raw material for producing products such as handicrafts and various kinds of culinary preparations. Not all business actors use technology as a means of promotion or marketing of their processed products. We need a media that accommodates this typical product of the city of Sampit, where the media is easy to use not only for business actors but also for the community. This Website-based promotional media was created by applying the stages contained in the Waterfall software development method according to Rosa and M. Salahuddin (2013), namely Analysis, Design, Coding and Testing, as well as PHP and MySQL programming languages ​​as databases. This research produces a website as a promotional medium for typical Sampit souvenirs that can be accessed by the general public.